2019
DOI: 10.1007/978-3-030-28764-1_27
|View full text |Cite
|
Sign up to set email alerts
|

Student’s Acceptance of Learning Management Systems: A Case Study of the National Open University of Nigeria

Abstract: This research examines the key factors that influence the acceptance of learning management systems (LMS') by students of the National Open University of Nigeria (NOUN). To achieve this, the constructs from previous studies on eLearning acceptance were adopted to develop a conceptual model. Based on the model, structural equation modeling (SEM) was applied to the data obtained from 384 students. The results indicated that instructor quality is a determinant of learning value and perceived usefulness; system qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
1
11
0
1
Order By: Relevance
“…In Nigeria, the National Policy on ICT recognizes the importance of ICT in the education sector (NITDA, 2012). Many stakeholders in the Nigeria higher education sector have started to appreciate the effectiveness of integrating technology in teaching and learning (Yakubu, Kah, & Dasuki, 2019). However, just like many developing countries, the uptake of the use of ICTs has been very slow with few universities having incorporated the use of technology, specifically LMS, for teaching and learning (Yakubu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, the National Policy on ICT recognizes the importance of ICT in the education sector (NITDA, 2012). Many stakeholders in the Nigeria higher education sector have started to appreciate the effectiveness of integrating technology in teaching and learning (Yakubu, Kah, & Dasuki, 2019). However, just like many developing countries, the uptake of the use of ICTs has been very slow with few universities having incorporated the use of technology, specifically LMS, for teaching and learning (Yakubu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many stakeholders in the Nigeria higher education sector have started to appreciate the effectiveness of integrating technology in teaching and learning (Yakubu, Kah, & Dasuki, 2019). However, just like many developing countries, the uptake of the use of ICTs has been very slow with few universities having incorporated the use of technology, specifically LMS, for teaching and learning (Yakubu et al, 2019). Also, the few institutions that have adopted the use of LMS have opted for proprietary software; this is especially true for public (governmentowned) universities.…”
Section: Introductionmentioning
confidence: 99%
“…Although our focus is primarily on identifying the implications for the process of developing a contextspecific pedagogical approach, our analysis also points to important ideas about the need to develop eLearning systems that stimulate interaction, facilitate engagement, and provide a meaningful learning experience, thereby emphasis issues often neglected in the literature (Olatuboson et al, 2015;Oyelere et al, 2016;Okocha et al, 2017;Yakubu et al, 2019;Okocha, 2019). We believe this is significant, as the analysis of the data has shown that the adoption of technology through a blended approach is not merely about how the technology can support the practice of education, but also about how the use of the technology can bring about a shift in our theoretical and conceptual formulations concerning non-western educational processes and practices (Reagan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Specific to Nigeria, the assumption is that the adoption of technology in education can bridge the gaps that exists in the system by providing quality education to all. In clearly articulating the trajectory of such efforts, a range of studies have analysed the potential and opportunities of blended learning (Anene et al, 2014;Adeoye, 2020); the approaches to planning, integration, and acceptance (Okocha, 2019;Aladejana and Olajide, 2019;Ukaigwa and Igbozuruike, 2020), and the conceptual experience of different stakeholders towards the blended approach (Olatuboson et al, 2015;Okocha et al, 2017;Yakubu et al, 2019). However, only a few studies attempt to examine how the adoption of technology has brought about stimulating social interaction, facilitated engagement, and improved instructional processes and learning outcomes (Olatuboson et al, 2015;Oyelere et al, 2016;Okocha, 2019).…”
Section: Blended Approaches To Learningmentioning
confidence: 99%
“…Currently, it is commonly seen that educational institutes operate their own Learning Management Systems (LMS) and provide various online smart learning features for a diverse group of students. An LMS is known as a web-based system that possesses an extensive range of pedagogical and course administration tools (Yakubu, 2019). Through these educational tools, LMS can facilitate group chats, discussions, document sharing, assignment submission, quizzes, grading and course evaluations (Bove, & A.,, & Conklin, S., 2020).…”
Section: Introductionmentioning
confidence: 99%